Regional destination attributes that attract domestic tourists: the role of man-made venues for leisure and recreation. Issue 6 (June 2021) - Camacho-Murillo, Andres; Gounder, Rukmani; Richardson, Sam
Abstract: This paper examines the influence of man-made attractions for leisure and recreation on domestic tourists' preferences amongst regional destinations, and the moderating role of these attractions on the negative effect of distance on tourists' choices. A mixed multinomial logit model is employed for 368 cities in Colombia grouped into 28 provinces. Factor analysis is utilised to identify the latent variable that groups several man-made attractions for leisure and recreation. Results show that domestic tourists' choices of a regional destination increase as the number of man-made attractions for leisure and recreation rises, although there is taste heterogeneity between tourists explained by their city of origin. Findings also show that the decline in domestic tourists' preferences for a regional destination due to increases in travel distance can be lessened through the construction and/or enhancement of man-made venues for leisure and recreation in the destination; a strategy that can serve to reduce monetary poverty in distant destinations that have attributes to attract tourists. Abstract : Domestic tourism; Man-made attractions; Tourism for leisure and recreation; Mixed logit model; Factor analysis.